Shape-dependent antimicrobial activities of silver nanoparticles - Cheon JY (Dove Medical Press, 2019)
Ja Young Cheon,1 Su Jun Kim,1 Young Ha Rhee,2 Oh Hyeong Kwon,3 Won Ho Park11Department of Advance Organic Materials and Textile System Engineering, Chungnam National University, Daejeon 34134, Korea; 2Department of Microbiology and Molecular Biology, Chungnam National University, Daejeon 34134, Korea; 3Department of Polymer Science and Engineering, Kumoh National Institute of Technology, Gumi 39177, KoreaPurpose: An important application of silver nanoparticles (Ag NPs) is their use as an antimicrobial and wound dressing material. The aim of this study is to investigate the morphological dependence on the antimicrobial activity and cellular response of Ag NPs.Materials and methods: Ag NPs of various shapes were synthesized in an aqueous solution using a simple method. The morphology of the synthesized Ag NPs was observed via TEM imaging. The antimicrobial activity of the Ag NPs with different morphologies was evaluated against various microorganisms (Escherichia coli [E. coli], Staphylococcus aureus [S. aureus], Pseudomonas aeruginosa [P. aeruginosa]). The antimicrobial activity of the Ag NPs was also examined according to the concentration in terms of the growth rate of E. coli.Results: The TEM images indicated that the Ag NPs with different morphologies (sphere, disk and triangular plate) had been successfully synthesized. The antimicrobial activity obtained from the inhibition zone was in the order of spherical Ag NPs > disk Ag NPs > triangular plate Ag NPs. In contrast, fibroblast cells grew well in all types of Ag NPs when the cell viability was evaluated via an MTT assay. An inductively coupled plasma mass assay showed that the difference in the antimicrobial activities of the Ag NPs was closely associated with the difference in the release rate of the Ag ions due to the difference in the surface area of the Ag NPs.Conclusion: The morphological dependence of the antimicrobial activity of the Ag NPs can be explained by the difference in the Ag ion release depending on the shape. Therefore, it will be possible to control the antimicrobial activity by controlling the shape and size of the Ag NPs.Keywords: silver nanoparticles, Ag NPs, different shape, antimicrobial activity, cell viability, ion release